2017
DOI: 10.1016/j.diii.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Added value of diffusion-weighted magnetic resonance imaging for the diagnosis of perianal fistula

Abstract: DWI has a significant added value compared to T2-weighted imaging alone in the diagnosis of perianal fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…DW imaging has therefore been proposed as an important alternative, owing to the fact that inflammatory lesions can be seen as high signal areas on DW imaging. The fistulous tracks appear hyperintense while the background signal is significantly suppressed on DW images; thus, the presence and extent of fistula can be detected clearly [23,35]. Studies have concluded that the conspicuity of fistulous tracks is better on DW-MRI than T2W images, thus increasing the sensitivity for its detection [23,35,36].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…DW imaging has therefore been proposed as an important alternative, owing to the fact that inflammatory lesions can be seen as high signal areas on DW imaging. The fistulous tracks appear hyperintense while the background signal is significantly suppressed on DW images; thus, the presence and extent of fistula can be detected clearly [23,35]. Studies have concluded that the conspicuity of fistulous tracks is better on DW-MRI than T2W images, thus increasing the sensitivity for its detection [23,35,36].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…These findings go in hand with Dohan et al [22] who reported an area under the ROC curve of 0.971 with a sensitivity of 100%, a specificity of 90 %, PPV of 93%, and NPV of 90% for an abscess diagnosis. Also, Cavusoglu et al [23] found the confidence scores for perianal fistula diagnosis using combination of gadolinium chelate-enhanced T1 and T2-WI were greater than T2-WI alone and confidence scores using the combination of DW-MRI and T2-WI were greater than T2-WI alone with greater sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Then, Yoshizako et al [21] who assessed the feasibility of using DW-MRI for evaluating perianal fistula activity documented that DW-MRI is a feasible method for evaluating perianal fistula activity with area under the ROC curve of 0.749. Thereafter, Cavusoglu et al [23] documented that DW-MRI has a significant added value compared to T2-WI alone in the diagnosis of perianal fistula and Baik et al [24] found combined DW-MRI and CE-T1WI might improve fistula conspicuity with comparable diagnostic performance to T2WI. Recently, Wang et al [25] reported that fractional anisotropy (FA) and ADC values for positive inflammation activity were significantly lower than those for negative inflammatory activity and concluded that FA and ADC values were instrumental in evaluating the activity of perianal fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…In MRI pelvis, T1 weighted, T2 weighted, short tau inversion recovery (STIR) and T1 post-contrast with fat suppression sequences are commonly used to evaluate fistula-in-ano [10]. Recently, the role of diffusion-weighted imaging (DWI) has also been evaluated [11]. However, MRI is an expensive modality and is time-consuming to perform.…”
Section: Introductionmentioning
confidence: 99%